2011
DOI: 10.1590/s1516-35982011000800023
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade física e sensorial da carne de cordeiros de três genótipos alimentados com rações formuladas com duas relações volumoso: concentrado

Abstract: IntroduçãoO mercado, potencialmente promissor para carne ovina no Brasil, aliado ao novo perfil dos consumidores, mais perceptíveis à qualidade, tem induzido o aprimoramento técnico e organizacional na atual cadeia produtiva. O desenvolvimento de técnicas adequadas de manejo nutricional para cordeiros em terminação que conduzam a modificações desejáveis no conteúdo dos ácidos graxos da carne tem promovido, em alguns casos, a depreciação nos atributos sensoriais da carne, a exemplo do aroma e sabor (Vasta & Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
1
11
0
17
Order By: Relevance
“…Higher or lower values for shear force, according to Sañudo et al (1997), can be found in younger animals according to the slaughter age, and perhaps, according to interactions among different rates of deposition of collagen and fat in the animal. This variation in results has been reported in the literature both for values similar to those found in the current study (LEÃO et al, 2012) and higher values (COSTA et al, 2011a;VIEIRA;FERNÁNDEZ, 2014).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Higher or lower values for shear force, according to Sañudo et al (1997), can be found in younger animals according to the slaughter age, and perhaps, according to interactions among different rates of deposition of collagen and fat in the animal. This variation in results has been reported in the literature both for values similar to those found in the current study (LEÃO et al, 2012) and higher values (COSTA et al, 2011a;VIEIRA;FERNÁNDEZ, 2014).…”
Section: Resultssupporting
confidence: 85%
“…In a pioneering study, Penny and Dransfield (1979) reported that muscles with shorter sarcomere result in tougher meat, which is influenced by the location of the muscle, carcass chilling speed (VIEIRA; FERNÁNDEZ, 2014), speed of proteolysis (HWANG et al, 2004), rigor mortis stage (COSTA et al, 2011a), and body weight at slaughter (MARTÍNEZ-CEREZO et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The literature describes variations in color scores, juiciness and water holding capacity between breeds (Hernández- Cruz et al, 2009;Costa et al, 2011). Osório et al (2008) argued that the most noticeable changes are related with physical aspects of meat, mainly the color because it has a direct impact on appearance and consumer acceptability.…”
Section: Breedmentioning
confidence: 99%
“…Maiores quantidades de gordura intra e intermuscular levarão a menores perdas de peso por cozimento (PPC), resultando em carnes mais suculentas, pois a gordura atua como barreira de proteção contra a perda da umidade (SAÑUDO et al,1997;COSTA et al, 2011 A cor do músculo é determinada pela quantidade de mioglobina e pelas proporções relativas desse pigmento, que pode ser encontrado na forma mioglobina reduzida (Mb, cor púrpura), oximioglobina (MbO2, cor vermelha) e metamioglobina (MetMb, cor marrom) (SILVA SOBRINHO et al, 2005). O aspecto visual da carne fresca é muito importante, já que a descoloração de sua superfície pode ser interpretada pelo consumidor como uma condição de insalubridade.…”
Section: Discussionunclassified
“…Os valores observados para L* e a* são mais elevados, enquanto os valores de b* são menores que aqueles observados por Costa et al (2011) (COSTA et al, 2011) e não estão relacionados diretamente a melhoria na qualidade da carne.…”
Section: Discussionunclassified